تأثير استعمال الوسائل السمعيّة البصريّة على نتائج تعليم مفردات اللغة العربية للفصل الرابع في المدرسة الإبتدائية الإسلامية الحكومية بارمبهان لمباسي بياكمبوه - Sartika, Fitria; Ritonga, Mahyudin (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
Low ability of students in understanding the vocabulary of Arabic one of them due to improper use of learning media. Similarly, in the fourth grader Islamic Elementary School Parambahan Lampasi Payakumbuh, that is, there are many daily results of the Arabic language vocabulary students who are below average. Therefore, it is necessary to test the media that is deemed interesting for the students that is audio visual media. The purpose of this research is to uncover the influence of the use of audio visual media to the outcome of learning vocabulary Arabic in class four at Islamic Elementary School Parambahan Lampasi Payakumbuh. The method used in this research is a quantitative method with the quasi-experimentation approach, the population of this research is the fourth graders at Islamic Elementary School Parambahan Lampasi Payakumbuh. Researchers took them as samples using the total sampling technique, since the fourth class consisted of two classes, namely fourth grade A and fourth grade B. Learning in experimental classes using audio visual media, while the control class without using media. The result of this study is that audio visual media can affect the learning of the language Mufradat Arabic positively to students in Islamic Elementary School Parambahan Lampasi Payakumbuh.